Strain-dependent phenotype of p130- and p107-deficient mice - LeCouter, Jennifer E. (My University, 1999)
For the development of many cell types, terminal differentiation and continued cell cycle progression are incompatible processes. Rb, p107 and p130 comprise a gene family encoding transcriptional regulators that act within a complex network to control exit from, and progression through the cell cycle. The distinct requirements for p130 and p107 were assessed in vivo using homologous recombination in embryonic stem (ES) cells. p130 expression is ubiquitous, although the level of expression varies between tissues. As well, its induction during neuronal cell differentiation is consistent with p130 function accompanying terminal differentiation. p130 deficiency was incompatible with embryo survival in the hybrid 129Sv;Balb/c genetic background. The mutant embryos died between E11-13 and exhibited striking delays in growth and development at 10.5 dpc with specific deficits in neurogenesis, somitogenesis and cardiogenesis. p130 appears to be required for the maintenance and survival of specific cell types, most notably neuronal cells. The data indicate that the p130 gene is essential for normal development, but in a strain-specific manner. On a hybrid 129Sv;C57B1/6 background, the p130 mutants exhibited no phenotype. The p107 mutants were viable and fertile, indicating that p107 function was adequately compensated by other proteins during development, potentially Rb and p130. The p107-/- mice did however exhibit a postnatal growth deficit and a diathetic myeloid proliferative disorder. The accelerated proliferation and cell-cycle kinetics of p107-/- EF indicated that p107 functions, in part, to regulate cyclin expression and cell cycle progression. p107-/- myoblasts also exhibited accelerated prliferation and aberrant in vitro differentiation. Lastly, the p107-/- phenotype was also dependent on the genetic strain, indicating the presence of modifying genes. The mice produced in these studies can be assessed for genes that modify the phenotypes in these different strains, potentially revealing epistatic relations to p107 and p130. Although both striking and subtle cell-specific phenotypes were exhibited, these experiments strongly reconfirm that functional overlap and compensation exist within the Rb family. The overlapping expression patterns and apparent functional relations indicate that p130, p107 and Rb regulate transitions in a concerted manner during cell proliferation, and cell cycle exit and entrance.
Keywords: Medical Sciences; Medical Sciences